Stress and coping experience in Nurse Residency Programs for new graduate nurses: A qualitative meta-synthesis - Han, Peng; Duan, Xia; Wang, Lingmin; Zhu, Xiaoping; Jiang, Jinxia (Frontiers in Public Health, 2022)
Objectives: To determine the stress experience and coping styles of new nurses during Nurse Residency Programs (NRPs) by identifying, appraising, and synthesizing data from the qualitative studies. Design: A systematic review and meta-synthesis of qualitative studies. Review Methods: Eleven databases were systematically searched for relevant publications in March 2022. All qualitative and mixed-method studies in English and Chinese that explored the stress and coping experience during NRPs of new graduate nurses were included. The qualitative meta-synthesis was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Two independent reviewers selected the studies and assessed the quality of each study. Meta-synthesis was performed to integrate the results. Results: A total of 13 studies revealed 13 sub-themes and three descriptive themes: multi-dimensional stressors, somatic and emotional responses, coping resources and coping methods. Conclusion: New nurses faced a lot of physical and emotional stress during NRPs, which had a negative impact on their physical and mental health. NRPs are a critical period for the career growth of new nurses. Effective management strategies must be implemented to improve nurse capacity, meet their needs, improve self-efficacy, and build organizational support, as this can improve the quality of clinical nursing and keep the enthusiasm and stability of the nursing team.